2006
DOI: 10.1002/bit.21301
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles and nanoparticles for drug delivery

Abstract: Particulate drug delivery systems have become important in experimental pharmaceutics and clinical medicine. The distinction is often made between micro-and nanoparticles, being particles with dimensions best described in micrometers and nanometers respectively. That size difference entails real differences at many levels, from formulation to in vivo usage. Here I will discuss those differences and provide examples of applications, for local and systemic drug delivery. I will outline a number of challenges of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
283
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(300 citation statements)
references
References 28 publications
4
283
0
3
Order By: Relevance
“…We found that, as a consequence of their low modulus, these discoid microparticles bypassed several in vivo filtration mechanisms, illustrated by animal survival and dramatic increases in elimination half-lives of particles with decreasing modulus. Such deformable and long-circulating particles may find utility in the fields of drug delivery and medical imaging, where long-circulation times and varied biodistributions are often desirable characteristics (6,16,17). Further, we expect these results will stand as an introduction for particle deformability as a vital design parameter that can affect the behavior of particles on both the microand nanoscales.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…We found that, as a consequence of their low modulus, these discoid microparticles bypassed several in vivo filtration mechanisms, illustrated by animal survival and dramatic increases in elimination half-lives of particles with decreasing modulus. Such deformable and long-circulating particles may find utility in the fields of drug delivery and medical imaging, where long-circulation times and varied biodistributions are often desirable characteristics (6,16,17). Further, we expect these results will stand as an introduction for particle deformability as a vital design parameter that can affect the behavior of particles on both the microand nanoscales.…”
mentioning
confidence: 89%
“…Beyond RBCs, cancer cells, especially metastatic cancer cells, are elastically softer than healthy cells, a characteristic that is believed to be integral to their ability to spread to new locations (1,4). Although much attention has been directed toward the enhancement of the circulation time of particles, including alterations of particle size (5,6), shape (7)(8)(9), and surface characteristics (10), the role played by deformability in the in vivo circulation profile of particles has not been well explored.…”
mentioning
confidence: 99%
“…Other features in which particle diameter affects the in vivo nanoparticle role are extravasation, targeting, circulation times, internalization, immunogenicity, degradation, flow properties, clearance and uptake mechanisms ( Fig. 2.10) (Kohane, 2007). Figure 2.10: Schematics of particle transport processes occurring in the human body which are determined by particle size.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Beyond particle chemistry, physical properties such as size (2,8) or shape (9,10) have been identified as key attributes that govern particle fate in a number of biomedical and biotechnological applications (2). In an attempt to mimic the complexity of biological particles, a number of increasingly sophisticated, multifunctional particles have been devised (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%